2000
DOI: 10.1034/j.1600-0765.2000.035006369.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase expression in periodontitis

Abstract: Recently, nitric oxide (NO) has been shown to be vital in inflammatory processes. Nitric oxide synthase (NOS) exists in three different isoforms, two constitutively produced with physiological roles, and an inducible form, iNOS, which is involved in inflammation. This study examined the localisation of iNOS in biopsies from patients with periodontitis using immunohistochemistry, and compared these with healthy tissue biopsies. Biopsies were obtained from 16 periodontitis patients undergoing periodontal surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
150
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 19 publications
11
150
1
9
Order By: Relevance
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionmentioning
confidence: 71%
“…NO has been implicated in the pathogenesis of apical infection [45], periapical granulomas [46], and inflamed human dental pulp [47]. Increased iNOS expression in gingiva was shown in periodontitis [20,22,26,28,31], ligature-induced periodontitis [27], experimental periodontitis [30,46], inflamed gingiva [23], localized aggressive periodontitis [21], and recently by our group in aggressive periodontitis (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although both NO and substance P, classical NANC neurotransmitters, are implied in both pathophysiology of chronic pain (Anbar & Gratt) and PD (Lappin et al, 2000) as well, including primary headache conditions (Anbar & Gratt), there are no studies acknowledged so far which investigate its behavior in patients the gingival expression of sP and NO since both are related to the mechanisms of persistent pain (Anbar & Gratt) and both are also related to the pathophysiology of PD (Lappin et al, 2000) and some primary headaches as well (Goodale, 1981). These analyses were made in the total sample and epithelial or connective tissues.…”
Section: Discussionmentioning
confidence: 99%